2012
DOI: 10.1590/s1516-35982012000700008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between genotypes of forage peanut in relation to agronomic and chemical traits

Abstract: -The objective of this study was to evaluate the genetic divergence of forage peanut in relation to agronomic and chemical traits in both rainy and dry seasons. This experiment was conducted with genotypes from the Forage Peanut Active Germoplasm Bank located in Embrapa Acre. Eighteen genotypes of forage peanut were used: 12 genotypes of A. pintoi, four genotypes of the A. repens species and two interspecific hybrids of A. pintoi × A. repens. The design was of randomized blocks with five replicates. All traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
3
9
0
1
Order By: Relevance
“…Accession 60Ar exhibited a high degree of ancestry from gene pool III. This result corroborates those obtained in studies by Gimenes et al (2000) and Menezes et al (2012), who found that accession 60Ar was grouped with A. pintoi accessions, confirming the proximity of this A. repens accession to A. pintoi.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Accession 60Ar exhibited a high degree of ancestry from gene pool III. This result corroborates those obtained in studies by Gimenes et al (2000) and Menezes et al (2012), who found that accession 60Ar was grouped with A. pintoi accessions, confirming the proximity of this A. repens accession to A. pintoi.…”
Section: Resultssupporting
confidence: 92%
“…characterized the bristle of the stigmatic surface and found four clusters, three of which clustered accessions of both species. Menezes et al (2012) studied the agronomic and bromatological characterization of the section Caulorrhizae and found six clusters, four of which consisted of A. pintoi and A. repens genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arachis pintoi , A. repens Handro and their hybrids present several features related to persistence in the pasture sward, and they differ from those of other forage legumes (Menezes et al ., ) in their tolerance to adverse management conditions, resistance to grazing and stoloniferous growth (having a strongly rooted stolon and well‐protected meristem growing points). Arachis persistence is also related to the presence of buried seed reserves (Assis et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…The DM averages ranged from 89.1 to 91.6% (Table 2) and corroborate MS values 88.70; 88.10 and 92.80% reported for perennial peanut hays. 2,7,12 Normally to be considered a hay foodstuff, it DM can be below 15% in order to avoid damage microorganisms proliferation. 10,13 Considering only the DM ( Table 2) the A. pintoi hay can be a forage source without contamination problems, if the storage conditions were adequate.…”
Section: Discussionmentioning
confidence: 99%